LANGUAGE SHIFT AND MAINTENANCE AMONG MIGRANT COMMUNITIES - Mirzahamdamova, Dilafruz (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
Language shift and maintenance are central issues in sociolinguistics, particularly within migrant communities where heritage languages coexist with dominant national languages. This paper explores how immigrant families navigate the tension between preserving their native tongue and adapting to the linguistic demands of their host country. Drawing on existing sociolinguistic theories and case studies from diverse contexts, the research highlights the sociocultural, educational, and generational factors that influence language practices. The methodology combines a review of secondary literature with a qualitative case study of migrant families in multilingual contexts. Findings indicate that while younger generations are more prone to adopt the dominant language, family networks, community institutions, and cultural identity play crucial roles in heritage language retention. The paper concludes by stressing the need for policies and community initiatives that support bilingualism and prevent the erosion of minority languages.